Моделі вибору периферійного забезпечення офісу з управління проектами - Плугіна, Тетяна Вікторівна; Щерба, Юрій Миколайович; Похитайло, Павло Олександрович (Eastern-European Journal of Enterprise Technologies, 2009)
In clause the task of a choice of the hardware of office on management of the projects is considered. The business - processes of office on management of the projects are considered. The mathematical model of a choice of a complex of hardware is offered in view of the requirements of business - processes.